Studi Literatur Manfaat Edukasi Berbasis Video Dalam Peningkatan Pengetahuan Perawatan Stoma - Sitti Salmawati; Saldy Yusuf; Takdir Tahir (Jurnal Keperawatan Muhammadiyah, 2019)
Objective: conduct a literature review on stoma video-based education to improve stoma care knowledgeMethod: The literature review was carried out by searching the results of scientific publications from the Pubmed, Science Direct, Google Schoolar, and Cochrane databases which were in the period from 2010-2017, English full text with the keyword "Ostomy", "Colostomy", " education "," education program "," educational media "," stoma care "," Selfcare "and" patient care "Results: Obtained 88 articles where 5  were included in the inclusion criteria.4 experimental studies, some with randomized controlled trials, 1 descriptive qualitative. research using educational methods with videos showed that education using videos significantly increased knowledge and abilities in stoma care.Conclusion: Providing video-based education can improve the knowledge of patients with stoma about how to treat stoma